Antara Sejarah Peteng dan Sejarah Weteng: Mengidentifikasi Objek Sengketa dalam Kisruh Keraton Kasepuhan Cirebon - Tendi, Tendi (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2023)
The conflict that occurred in Keraton Kasepuhan in 2020 was not the first dispute to occur within the palace. However, the 2020 conflict was perhaps the biggest as it affected the life of the Cirebon palace. In that conflict, the term sejarah petheng became an important thing that was always mentioned by the community, because the concept seemed to be used as a weapon to bring down the ruling family. This article seeks to reveal the motives behind the conflict. In this study, the author conducted research using the historical method. From this study, it is known that the background of the Kasepuhan Palace conflict in 2020 is not only about pribawa and the genealogical truth of the ruler, but also based on disputes over palace assets. In other words, the motive behind the conflict is not only petheng history, but also wetheng history